Arteriovenous fistula maturation and the influence of fluid dynamics. (November 2020) - Colley, Eamonn; Simmons, Anne; Varcoe, Ramon; Thomas, Shannon; Barber, Tracie
Arteriovenous fistula creation is the preferred vascular access for haemodialysis therapy, but has a large failure rate in the maturation period. This period generally lasts 6 to 8 weeks after surgical creation, in which the vein and artery undergo extensive vascular remodelling. In this review, we outline proposed mechanisms for both arteriovenous fistula maturation and arteriovenous fistula failure. Clinical, animal and computational studies have not yet shown a definitive link between any metric and disease development, although a number of theories based on wall shear stress metrics have been suggested. Recent work allowing patient-based longitudinal studies may hold the key to understanding arteriovenous fistula maturation processes.